2020
DOI: 10.1002/ajhb.23487
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the frequency of third molar agenesis according to different age groups

Abstract: Purpose Third molars (M3s) are the most common congenitally missing teeth. The aim of this study was to compare the frequency of M3 agenesis in two different age groups. Methods This study examined the panoramic radiographic images of 1036 patients. Two groups, each consisting of 518 patients, were arranged based on age ranges. The patients aged 12 to 19 years were in the first group and those 20 years and older were in the second group. The frequency of M3 agenesis was examined in both age groups. The distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…High reproducibility is one of the main reasons for preferring this method to the simple observation of the eruptive sequence of the teeth, which is unreliable and not useful for the goal of determining the adult age [ 28 ]. This is because the assessment of third molar eruption is not reliable due to the absence of a precise age of eruption and the high presence of inclusions and agenesis [ 29 ]. A study by Gambier et al reported a high probability that when the third molars have erupted in the arch, the subject is over 18 years old, but the authors themselves stated that the assessment of the eruption of M3s alone was not sufficient for the determination of whether or not an individual is aged 18 years or older [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…High reproducibility is one of the main reasons for preferring this method to the simple observation of the eruptive sequence of the teeth, which is unreliable and not useful for the goal of determining the adult age [ 28 ]. This is because the assessment of third molar eruption is not reliable due to the absence of a precise age of eruption and the high presence of inclusions and agenesis [ 29 ]. A study by Gambier et al reported a high probability that when the third molars have erupted in the arch, the subject is over 18 years old, but the authors themselves stated that the assessment of the eruption of M3s alone was not sufficient for the determination of whether or not an individual is aged 18 years or older [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…La agenesia es el término que se usa cuando el paciente tiene ausencia congénita de uno o más dientes, puede estar asociado a enfermedades o síndromes (8), sin embargo, hay reportes de agenesia en pacientes no sindrómicos y se relacionan a la evolución humana, llamada también ausencia congénita de un diente o hipodoncia (3). La frecuencia de agenesia de terceros molares en pacientes no sindrómicos ha sido reportada en la literatura a nivel mundial, como González en Portugal 19.1% (4), Ramiro en España 13.11% (5), Pamukcu en Turquía 24.9% (6), Mishra en India 36.8% (7). A nivel Latinoamericano en Ecuador: Huilcarema 60% (9), Solis 16.67% (10), Martínez 45% (11).…”
unclassified